2004
DOI: 10.1242/jcs.01349
|View full text |Cite
|
Sign up to set email alerts
|

Gyp5p and Gyl1p are involved in the control of polarized exocytosis in budding yeast

Abstract: We report here elements for functional characterization of two members of the Saccharomyces cerevisiae Ypt/Rab GTPase activating proteins family (GAP): Gyp5p, a potent GAP in vitro for Ypt1p and Sec4p, and the protein Ymr192wp/APP2 that we propose to rename Gyl1p (GYp like protein). Immunofluorescence experiments showed that Gyp5p and Gyl1p partly colocalize at the bud emergence site, at the bud tip and at the bud neck during cytokinesis. Subcellular fractionation and co-immunoprecipitation experiments showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 40 publications
(39 reference statements)
5
32
0
Order By: Relevance
“…In this way, overexpression of Gyp5p and Gyl1p mimics loss of Rvs167p (84). Another study, however, found that Gyp5p and Gyl1p function in post-Golgi apparatus traffic (see above) (33). Perhaps Gyp5p and Gyl1p function in early steps of the secretory pathway with Ypt1p and in late steps of the secretory pathway with Sec4p.…”
Section: Roles Of Rvs161p and Rvs167p In The Secretory Pathwaymentioning
confidence: 94%
See 3 more Smart Citations
“…In this way, overexpression of Gyp5p and Gyl1p mimics loss of Rvs167p (84). Another study, however, found that Gyp5p and Gyl1p function in post-Golgi apparatus traffic (see above) (33). Perhaps Gyp5p and Gyl1p function in early steps of the secretory pathway with Ypt1p and in late steps of the secretory pathway with Sec4p.…”
Section: Roles Of Rvs161p and Rvs167p In The Secretory Pathwaymentioning
confidence: 94%
“…Loss of Gyp1p and Gyl1p, either singly or in combination, did not result in Rvs phenotypes with the possible exception of bipolar bud site selection. Furthermore, overexpression of Gyp5p and Gyl1p did not perturb actin patch polarization or endocytosis, so the inhibitory effect seems to be restricted to ER-to-Golgi apparatus transport (33,84,317).…”
Section: Roles Of Rvs161p and Rvs167p In The Secretory Pathwaymentioning
confidence: 95%
See 2 more Smart Citations
“…We have found that the rvs delete strains have synthetic growth defects in combination with two genes involved in vesicle trafficking from endoplasmic reticulum (ER) to Golgi, sec22⌬ and rud3⌬ (Newman and Ferro-Novick, 1990;Kim, 2003), suggesting that the Rvs proteins may be required for proper ER-to-Golgi trafficking. Additional evidence to support a role for Rvs167p in ER-to-Golgi vesicle trafficking comes from screens for proteins that interact with the SH3 domain of Rvs167p: the Rvs167p SH3 domain has been shown to bind to at least one protein involved in vesicle trafficking from ER to Golgi: Gyp5p (Bon et al, 2000;Ho et al, 2002;Chesneau et al, 2004;Friesen et al, 2005) as well as the Gyp5p-interacting protein Gyl1p (Chesneau et al, 2004;Friesen et al, 2005). In addition, the finding that RVS167 and RVS161 have synthetic genetic interactions with VPS21, a gene involved in the delivery of vacuolar and endocytosed proteins to the vacuole (Gerrard et al, 2000; interaction with RVS167 reported previously by SingerKrü ger and Ferro-Novick, 1997) suggests a role for Rvs161p-167p in multiple vesicle-mediated functions.…”
Section: Vesicle Traffickingmentioning
confidence: 99%